Investigating the relationship between demographic characteristics on stress and self-efficacy of surgical technology students - Samaneh Dehghan abnavi, Hamed Parnikh , Seyede Fatemeh Nourani, Zahra Movahedni, Afsaneh Poudineh, Ahmad Ghadami (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background and Aim: Clinical education has a special importance in the operating room education system. Every clinical experience is not merely learning a specific knowledge or practical skill. It also increases the student’s confidence in his / her professional abilities. The aim of present study is to investigate the relationship between demographic characteristics and stress and self-efficacy of surgical technology students. Materials and Methods: In this two-stage randomized controlled clinical trial (before and after), 50 bachelor operating room students studying in the 4th, 6th and 8th semesters were randomly allocated to the experimental and control groups. Craniotomy surgery educational video was displayed for the experimental group before the surgery and the control group received routine education. Data collection instruments were two researcher-made questionnaires, including perceived stress scale (PSS) and evil Sher self-efficacy scale. They were used after confirming their reliability and content validity. Data were analyzed using SPSS 16 software through descriptive and analytical tests at a significant level of 0.05. Results: No significant relationship was found between students' age, GPA and their mean scores of perceived stress and self-efficacy in the control and intervention groups (P-value > 0.05). No significant relationship was found between students' gender and semester and their mean perceived stress and self-efficacy scores in the control and intervention groups (P-value> 0.05).